Gerakan “Aku Senang Membaca” Melalui Pembentukan Taman Baca Anak Serta Pelatihan Membaca dan Health Literacy - Nurhasnah; Viviandhari, Daniek; Maifitrianti (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2022)
Indonesian children still have limited access to books, and reading activities have not become a culture in Indonesia. This problem worsens with the Covid-19 pandemic because many schools were closed or changing the method to learning from home. In addition to reading, health literacy is also crucial during this pandemic. This service activity aims to increase interest in reading through training and establishing the children's reading park. The method used was training and diffusion of science and technology. The training was conducted online through video conferencing applications and live streaming via popular video sites. Evaluation of activities was carried out using a pre-test and post-test. More than 80 participants joined the training activities. From the questionnaire results, there was an increase in the average score of the participants after receiving the training. The children's reading park has been formed and is ready to be opened to the public. The procurement of books was carried out through grants from donors, and more than 300 reading books were collected.